2021
DOI: 10.1308/rcsann.2020.7117
|View full text |Cite
|
Sign up to set email alerts
|

Profunda femoris mycotic aneurysm as a complication of bacterial endocarditis: a case report and review of the literature

Abstract: Profunda femoris aneurysms account for only 0.5% of all peripheral artery aneurysms. This case documents a profunda femoris mycotic aneurysm (MA) in a 47-year-old woman, three years post-treatment of bacterial endocarditis. The patient underwent an open surgical excision of the aneurysm with antibiotic cover and made a successful recovery. A literature review was carried out to look at other MA cases to summarise the most common presentations, infective agents and management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…3 In our literature review only five cases were reported involving PFA being of a mycotic origin with only two being in the modern era (which is defined by the era of widespread use of endovascular treatment modalities) (Table 1). [7][8][9][10][11] With the first case being reported on a postmortem examination of a patient who had IE and leg pain in 1890, by Sir Brice Duckworth where a ruptured PFA aneurysm was found. 12 No established guidelines exist on the management of PFA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In our literature review only five cases were reported involving PFA being of a mycotic origin with only two being in the modern era (which is defined by the era of widespread use of endovascular treatment modalities) (Table 1). [7][8][9][10][11] With the first case being reported on a postmortem examination of a patient who had IE and leg pain in 1890, by Sir Brice Duckworth where a ruptured PFA aneurysm was found. 12 No established guidelines exist on the management of PFA aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the cases reported on PFA MAs only a single recent case was managed using an endovascular approach, with all older cases using an open surgical approach. 4,8,9,10,11 Accordingly, few studies have described endovascular approaches either by stenting or embolization for PFA aneurysms as a whole, in both mycotic and non-MAs. In a recent study performed by Khalid et al In 2014 on a successfully repaired non-mycotic ruptured PFA pseudo-aneurysm using a stent graft similar to our approach, they reported in their review that endo-vascular approach using stent graft was performed on other cases of PFA non-MAs with success and can be an alternative to open surgical approach.…”
Section: Discussionmentioning
confidence: 99%